Depletion of gut microbiota induces skeletal muscle atrophy by FXR-FGF15/19 signalling. (1st January 2021) - Qiu, Yixuan; Yu, Jiaming; Li, Yi; Yang, Fan; Yu, Huiyuan; Xue, Mengjuan; Zhang, Fan; Jiang, Xin; Ji, Xueying; Bao, Zhijun
Abstract: Background: Recent evidence indicates that host-gut microbiota crosstalk has nonnegligible effects on host skeletal muscle, yet gut microbiota-regulating mechanisms remain obscure. Methods: C57BL/6 mice were treated with a cocktail of antibiotics (Abx) to depress gut microbiota for 4 weeks. The profiles of gut microbiota and microbial bile acids were measured by 16S rRNA sequencing and ultra-performance liquid chromatography (UPLC), respectively. We performed qPCR, western blot and ELISA assays in different tissue samples to evaluate FXR-FGF15/19 signaling. Results: Abx treatment induced skeletal muscle atrophy in mice. These effects were associated with microbial dysbiosis and aberrant bile acid (BA) metabolism in intestine. Ileal farnesoid X receptor (FXR)-fibroblast growth factor 15 (FGF15) signaling was inhibited in response to microbial BA disturbance. Mechanistically, circulating FGF15 was decreased, which downregulated skeletal muscle protein synthesis through the extracellular-signal-regulated protein kinase 1/2 (ERK1/2) signaling pathway. Treating Abx mice with FGF19 (human FGF15 ortholog) partly reversed skeletal muscle loss. Conclusions: These findings indicate that the BA-FXR-FGF15/19 axis acts as a regulator of gut microbiota to mediate host skeletal muscle.